Hip Joint Restoration : Worldwide Advances in Arthroscopy, Arthroplasty, Osteotomy and Joint Preservation Surgery - McCarthy, Joseph C.; Noble, Philip C.; Villar, Richard N. (Springer New York : Imprint: Springer, 2017)
Hip Joint Restoration is a comprehensive yet practical guide to the basic science and clinical applications of arthroscopy, arthroplasty, osteotomy and preservation surgery for the treatment of diseases and conditions of the hip. This generously illustrated text offers a comprehensive introduction to essential features of hip evaluation, the medical management of hip procedures, and treatment of specific conditions, and covers practical topics such as surgical anatomy of the hip, surgical approaches, instrumentation, and indications for arthroscopy and other surgical procedures aimed at restoration of the hip joint. Additional chapters cover clinical outcomes and equality of life following hip surgery, the current state of research and education of arthroscopic hip procedures throughout the world, other topics such as complications and rehabilitation in different patient populations. This book will be a useful resource for Orthopedic Surgeons and Osteopaths who perform open and arthroscopic hip preservation and total joint replacement, as well as for orthopedic residents and researchers.- Resumé vydavatel